PENGARUH NILAI EMOSIONAL, NILAI SOSIAL, NILAI KUALITAS DAN NILAI FUNGSIONAL TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK TVS DI KOTA BENGKULU - Diah Khairiyah; Melda Yunita (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
The purpose of this study was to know the effect of emotional value, social value, quality value and functional value to the purchasing decision of TVS motorcycle in Bengkulu city. The sample in this study using many as 30 persons data analysis using multiple linear regression method. From the Anova table above obtained significant value (sig) 0,000. Significantly correlated to the alpha value of 0.05, can be interpreted from the results of significant value 0.000 <0.05, due to the significant value of 0.000 is smaller than 0.05, it means that Ha is accepted. It was concluded that ha received means a significant difference between the value of x to the y value to the purchasing decision. The results of significant value t (X 1 ) is 0.004, Social Value Factor (X2) is 0.005, Factor Value Quality (X3) is 0.009, and the Functional Rating Factor (X4) is 0.000. If these values correlated with the alpha of 0.05 means the result is smaller then Ha acceptable means there is significant influence value (X) to the purchasing decision (Y).